2016
DOI: 10.1016/j.cbi.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cocaine hydrolase engineered from human butyrylcholinesterase on metabolic profile of cocaine in rats

Abstract: Accelerating cocaine metabolism through enzymatic hydrolysis at cocaine benzoyl ester is recognized as a promising therapeutic approach for cocaine abuse treatment. Our more recently designed A199S/F227A/S287G/A328W/Y332G mutant of human BChE, denoted as cocaine hydrolase-3 (CocH3), has a considerably improved catalytic efficiency against cocaine and has been proven active in blocking cocaine-induced toxicity and physiological effects. In the present study, we have further characterized the effects of CocH3 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Strategies to deliver degradative enzymes have also been proposed for cocaine use disorders, and research is ongoing to develop stable, long-lasting forms of cocaine-degrading enzymes, including cocaine esterase, cocaine hydrolase (148)(149)(150)(151), and butyrylcholinesterase (152). Preclinical evidence has shown that these fusion proteins increase cocaine's metabolism (153,154).…”
Section: Promising Pharmacological Targetsmentioning
confidence: 99%
“…Strategies to deliver degradative enzymes have also been proposed for cocaine use disorders, and research is ongoing to develop stable, long-lasting forms of cocaine-degrading enzymes, including cocaine esterase, cocaine hydrolase (148)(149)(150)(151), and butyrylcholinesterase (152). Preclinical evidence has shown that these fusion proteins increase cocaine's metabolism (153,154).…”
Section: Promising Pharmacological Targetsmentioning
confidence: 99%
“…In addition, our most recently reported study demonstrated a novel protein form of E12–7 (or CocH3), denoted as CocH3-Fc or the catalytic antibody analog, which is an Fc-fused CocH3 dimer (CocH3-Fc) constructed by using CocH3 to replace the Fab region of human immunoglobulin G1. A single dose of CocH3-Fc significantly accelerated cocaine metabolism in rats after 20 days and, hence, blocked cocaine-induced physiological and toxic effects for a long period of time .…”
Section: Resultsmentioning
confidence: 99%
“…The sample extraction method used in this study was established in our previous studies [14, 35]. Briefly, internal standard (IS) solution (0.1 µM for each IS) with a volume equal to that of the whole blood was added to each blood sample.…”
Section: Methodsmentioning
confidence: 99%